A Case of Nivolumab‐Induced Myositis. (18th November 2016) - Fox, Eric; Dabrow, Michael; Ochsner, Greg
Abstract : Nivolumab (Opdivo) is a monoclonal antibody classified as an immune modulator. A case is presented of nivolumab‐induced myositis, an unlisted side effect.